Physical and Mechanical Properties of Geopolymers with the Addition of NaOH modified Bemban Fiber (Donax Canniformis) - Haryanti, Ninis Hadi; Chairunnisa, Nursiah; Pratiwi, Ade Yuniati; Nurwidayati, Ratni; Krasna, Wiku Adiwicaksana (Engineering, Technology & Applied Science Research, 2025)
The increasing demand for sustainable and eco-friendly materials has driven research into natural resource utilization. This study explores the development of geopolymer mortar incorporating fly ash, bemban fiber, and natural kaolin minerals. Due to its hydrophilic nature, bemban fiber requires alkalization treatment to enhance bonding strength within the geopolymer matrix. This research investigates the effect of 3% NaOH alkalization for 2 hours on the fiber’s properties. The results indicate that alkalization significantly enhances the physical and mechanical performance of bemban fiber. The optimal composition of 1.5% bemban fiber with a 70:30 metakaolin-to-fly ash ratio improves key properties, including water absorption (2.75%), porosity (5.80%), compressive strength (32.58 MPa), and splitting tensile strength (10.78 MPa). These findings are supported by Fourier Transform Infrared Spectroscopy (FTIR), which confirms geopolymerization through Si-O-Si asymmetric stretching vibrations at 974 cm⁻¹. Additionally, X-Ray Diffraction (XRD) analysis identifies a dominant quartz phase, while Scanning Electron Microscopy (SEM) reveals strong fiber-matrix bonding. This study highlights the potential of bemban fiber-reinforced geopolymers as a sustainable alternative for cement-based materials, promoting green construction practices.